Evaluating Landscape Degradation Along Climatic Gradients During the 1930s Dust Bowl Drought From Panchromatic Historical Aerial Photographs, United States Great Plains - Bolles, Kasey C.; Forman, Steven L. (Frontiers in Earth Science, 2018)
The U.S. Great Plains (USGP) are some of the most productive rangelands globally and a significant carbon sink for the atmosphere, but grassland response to precipitation is highly variable and poorly constrained over time and space. There is a rich historical aerial photographic record of the USGP which provides an unparalleled view of past landscapes and allows for evaluation of surficial response to drought beyond the satellite record, such as during the 1930s Dust Bowl Drought (DBD). This study classified the extent and loci of surficial denudation from seamless mosaics of radiometrically-corrected and georectified digitized aerial negatives acquired in the late 1930s from six counties distributed across USGP ecoregions. The dominant sources of degradation found for sites east of the 100th meridian are cultivated fields and fluvial deposits, associated with woody vegetation response to water availability in uncultivated areas. For sites to the west, denuded surfaces are predominantly eolian sandsheets and dunes, correlated with intensity of drought conditions and reduced plant diversity. Discrete spatial signatures of the drought are observed not only within the classically recognized southern Dust Bowl area, but also in the northern and central plains. Statistical analyses of site variability suggest landscape response to the DBD is most strongly influenced by the arid–humid divide and severity of precipitation and temperature anomalies. With a projected increase 21st century aridity, eolian processes cascading across western grasslands, like during the Dust Bowl, may significantly impact future dust particle emission and land and carbon storage management.